Four gland parathyroidectomy without reimplantation in patients with chronic renal failure. Issue 954 (5th April 2005) - Saunders, R N; Karoo, R; Metcalfe, M S; Nicholson, M L
Abstract : Background: The optimal surgical management of patients in end stage chronic renal failure with secondary hyperparathyroidism is controversial. One approach advocated is four gland parathyroidectomy without reimplantation. The aim of this study was to review the medium term results of this procedure. Methods: Fifty four consecutive patients with end stage chronic renal failure and secondary hyperparathyroidism who had a four gland parathyroidectomy without reimplantation were studied. The procedure was performed by a single surgeon with a median (range) follow up of 29 (0–70) months. Results: Most patients (76%) developed postoperative hypocalcaemia but this was easily treated and doses of long term drugs necessary to prevent this were low. Pre-operative bone symptoms, hypercalcaemia, hyperphosphataemia, and an increased alkaline phosphatase were improved or resolved in most patients. Thirteen (24%) patients had an undetectable postoperative parathyroid hormone (PTH), (6 of 12 (50%) with a functioning renal transplant and 7 of 42 (17%) who required dialysis, p = 0.02). Median (range) postoperative PTH values in these groups were 0.1 (0.1–31) compared with 1.0 (0.1–24) pmol/l (p = 0.085) respectively. The remaining 41 of 54 (76%) patients had residual PTH secretion and postoperative hyperparathyroidism was identified in eight (15%) patients with only two requiring neck re-exploration. Conclusion: Four gland parathyroidectomy without reimplantation produced good medium term biochemical and clinical results. Most patients had minor residual PTH secretion that may contribute to this and mitigate concerns regarding adynamic bone disease. Endogenous PTH secretion is only completely lost in a few patients but occurs more often in those with a functioning renal transplant. Bone densitometry is required to investigate the long term impact of this procedure.